Anthropometric normality in adults: the geographical and socio-economic paradox of the nutritional transition in Brazil Normalidade antropométrica de adultos: o paradoxo geográfico e socioeconômico da transição nutricional no Brasil - Malaquias Batista Filho; Teresa Cristina Miglioli; Marcela Carvalho dos Santos (Instituto Materno Infantil de Pernambuco, 2007)
OBJECTIVES: to consolidate secondary data and provide some as yet unpublished information on changes in the nutritional status of Brazilian children, and, principally, adults, from an anthropometrical point of view as evaluated in the course of the most recent surveys, laying emphasis on geographical and socio-economic features. METHODS: tables and graphs were used to consolidate data published by the Brazilian Institute of Geography and Statistics and from other sources, along with estimates for results not included in these original documents. Preliminary data from two as yet unpublished studies were also included. RESULTS: it was shown that, alongside the decline in malnutrition in children there are signs of an epidemic increase in obesity and overweight in adults. This is characteristic of the change in epidemiological profile associated with the nutritional transition. There is an apparent paradox that the highest frequencies for normal anthropometric measurements in adults were found in the poorer North and Northeast regions of Brazil. These results were even found in localities with very low indices for human development in the Northeast region. The best anthropometric situation for adult populations in Brazil was found in families with a low income (less than ¼ of one minimum wage per household per capita, with a prevalence rate twice as high among adult males in comparison with the higher household income group). CONCLUSIONS: the results for nutritional anthropo-metry among adults, showing more normal measurements among the low-income population, reflect a peculiar phase in epidemiological terms in the process of the nutritional transition in the country, which constitutes a paradox arising in these specific circumstances, which is probably temporary. OBJETIVOS: consolidar dados secundários e algumas informações ainda inéditas sobre a evolução antropométrica de estado nutricional de crianças brasileiras e, principalmente de populações adultas avaliadas em inquéritos mais recentes, enfatizando-se aspectos geográficos e socioeconômicos. MÉTODOS: foi feita uma consolidação em tabelas e gráficos, de publicações do Instituto Brasileiro de Geografia e Estatística e de outras fontes, com estimativas adicionais de resultados não incluídos nos trabalhos originais. Incorporação de dados preliminares de duas pesquisas ainda não publicadas. RESULTADOS: demonstra-se que, ao lado do declínio da desnutrição em crianças assinalou-se uma expansão epidêmica do sobrepeso e obesidade em adultos, caracterizando a mudança de perfis epidemiológicos que demarcam a transição nutricional. O aparente paradoxo de que as freqüências mais elevadas de normalidade antropométrica em adultos foram encontradas nas regiões mais pobres do Norte e Nordeste do Brasil, resultados que se reproduzem, em localidades com índices muito baixos de desenvolvimento humano do Nordeste. Descreve-se que, a melhor situação antropométrica de populações adultas no Brasil foi encontrada nas famílias de mais baixa renda (menos de ¼ de salário mínimo familiar per capita, com uma razão de prevalência duas vezes maior entre os homens adultos quando comparados com o grupo de renda familiar mais elevada). CONCLUSÕES: os resultados da antropometria nutricional de adultos, favorecendo as populações de baixa renda, refletem um momento epidemiológico peculiar do processo de transição nutricional do país, configurando um paradoxo circunstancial e provavelmente temporário.